Kropskultur i Grønland - set med danske øjne - Vinther, Solveig Skovmose (Forum for Idræt, 2007)
Artiklen belyser det koloniale og postkoloniale forhold mellem Grønland og Danmark og tegner et billede af danskerne syn på grønlandsk kropskultur gennem tiden. Solveig S. Vinther: Body Culture in Greenland – seen from Denmark Since the formal end of colonialism, great emphasis has been put on research in postcolonialism and postcolonial issues. The basic idea in this kind of research is that colonisation is not only a matter of war, violence, and power relations; we also need to consider changes at a more unspoken and unheeded level. In Denmark however, the term Empire has never really been part of the Danish self-image, and only a small amount of postcolonial research have been conducted that focus specifically on the relationship between Denmark and its former colonies. This article will look at the ways in which the Danish colonisers have described the body culture of the Greenlanders through time. The postcolonial aspect of the project will centre on the ways in which the relations between the colonisers and the colonised can be read in the literature of the colonisers. The term Polarism will be introduced to develop an understanding of the Danish discourses describing the body culture of Greenland. The article will hopefully begin to answer some of the unanswered – and unasked – questions concerning the relationship between Denmark and Greenland through an analysis of games, sports and body culture and their representation in the colonial and postcolonial descriptions of Greenland.